The Provision of Education and Employment Support At the Outreach and Support in South London (OASIS) Service for People at Clinical High Risk for Psychosis - Tognin, Stefania; Grady, Lara; Ventura, Serena; Valmaggia, Lucia; Sear, Victoria; McGuire, Philip; Fusar-Poli, Paolo; Spencer, Tom J. (Frontiers in Psychiatry, 2019)
Clinical services for the early detection of individuals at clinical high risk of psychosis, such as Outreach and Support in South-London (OASIS), have been successful in providing psychological intervention and psychosocial support to young people experiencing emerging signs of serious mental disorders. Despite this, several studies have repeatedly shown that vocational and functional recovery in the clinical high risk for psychosis population is still low. This study aimed at evaluating the presence and nature of educational and employment focused interventions within the OASIS service, in order to inform research and clinical interventions aimed at supporting young people with early signs of psychosis on their path to vocational recovery. The specific objectives were to compare current practice (i) to standards defined by the National Institute of Care Excellence guidelines; and (ii) to principles defined by Individual Placement and Support (IPS). Nine Standards of practice were derived. The OASIS caseload electronic records entered between January 2015 and January 2017 were manually screened. Data collected include sociodemographic, assessment of employment and educational status and support needs, interventions received, contacts with schools, employers and external vocational providers, employment and educational status. Standards were considered as “met” if they were met for at least 90% of clients. Results suggest that, 2 out of 9 standards were met while the remaining standards were only partially met. In particular, support provided was always focused on competitive employment and mainstream education and support was always based on people’s interest. Implications for clinical and research practice are discussed.